The Implementation of the Teaching at Right Level (TaRL) Aproach to Enhance Students Interest and Learning Outcomes in Qira’ah Skills at Malang Islamic Senior High School - Azhari, Muhammad; Ainin, Moh; Alnabiil, Ach. Rifqiy (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2025)
This study aims to examine the effectiveness of the Teaching at the Right Level (TaRL) approach in enhancing students’ interest and learning outcomes in reading skills among Grade XI E students at Islam Malang Senior High School.  The research employed a classroom action research design involving 30 students as participants.  Data on student interest were collected through multiple-choice questionnaires. At the same time, learning outcomes were measured across two cycles, each consisting of planning, implementation, observation, and reflection stages based on students' proficiency levels.  The results indicated an increase in student interest, with questionnaire scores rising from 68.5% in the pre-cycle to 76.3% in the post-cycle.  Learning outcomes also showed significant improvement across all proficiency groups.  In the beginner group, average scores increased from 56.9 (pre-cycle) to 80.5 (cycle one) and 93.9 (cycle two).  The intermediate group improved from 86 (pre-cycle) to 88 (cycle one) and 91 (cycle two).  The advanced group showed consistently high performance, rising from 96.5 (pre-cycle) to 100 in both subsequent cycles.  These findings demonstrate that the implementation of the TaRL approach positively impacted both student interest and reading proficiency in Arabic.